CryoSat instrument performance and ice product quality status. Issue 6 (15th September 2018) - Bouffard, Jerome; Webb, Erica; Scagliola, Michele; Garcia-Mondéjar, Albert; Baker, Steven; Brockley, David; Gaudelli, Julia; Muir, Alan; Hall, Amanda; Mannan, Rubinder; Roca, Mònica; Fornari, Marco; et al.
Abstract: Over the past 20 years, satellite radar altimetry has shown its ability to revolutionise our understanding of the ocean and climate. Previously, these advances were largely limited to ice-free regions, neglecting large portions of the Polar Regions. Launched in 2010, the European Space Agency's (ESA) polar-orbiting CryoSat satellite was specifically designed to measure changes in the thickness of polar sea ice and the elevation of the ice sheets and mountain glaciers. To reach this goal, the CryoSat products have to meet the highest performance standards, achieved through continual improvements of the associated Instrument Processing Facilities. Since April 2015, the CryoSat ice products are generated with Baseline-C, which represented a major processor upgrade. Several improvements were implemented in this new Baseline, most notably the release of freeboard data within the Level 2 products. The Baseline-C upgrade has brought significant improvements to the quality of Level-1B and Level-2 products relative to the previous Baseline-B products, which in turn is expected to have a positive impact on the scientific exploitation of CryoSat measurements over land ice and sea ice. This paper provides an overview of the CryoSat ice data quality assessment and evolutions, covering all quality control and calibration activities performed by ESA and its partners. Also discussed are the forthcoming evolutions of the processing chains and improvements anticipated in the next processing Baseline.